Advances in the diagnosis and treatment of iron deficiency and iron deficiency anemia - Alvarado, Carlos S. (2022)
Iron deficiency (ID) and iron deficiency anemia (IDA) are still major health problems worldwide, affecting especially preschool children and pregnant women. The objectives of this article are: a) To describe the laboratory tests for diagnosing IDA and the factors that may influence results of the serum ferritin and the other iron biomarkers ; b) To present advances in iron metabolism, i.e. the critical regulatory role of hepcidin in the absorption and utilization of iron ; c) To describe the impact this new knowledge has had in the design of clinical investigations comparing the absorption of iron following oral supplementation given in consecutive days vs. alternate days schedules; and, d) To describe the clinical situations in which intravenous iron is indicated as secondary or first-line treatment. The concepts expressed and the suggestions made in this article are based on updated literature and the clinical experience of the authors.